Viable low temperature shape memory alloys based on Ni-Ti-Hf formulations. (15th April 2019) - Benafan, O.; Bigelow, G.S.; Garg, A.; Noebe, R.D.
Abstract: Ni-rich NiTiHf alloys with Hf content from 1 to 12.5 at.% were evaluated for their potential as low temperature shape memory alloys. At 51 at.% Ni, a minimum in transformation temperature was observed at 8 at.% Hf with a martensite finish temperature of −140 °C. Beyond 8 at.% Hf, transformation temperatures started to rise. Increasing Ni content from 50.3 to 52 at.% resulted in a resilient alloy with remarkable dimensional stability and transformation strain in the range of 3% in compression. Work outputs above 30 J/cm 3 in some of these alloys attest to their suitability for low temperature actuator applications. Graphical abstract: Unlabelled Image